Involvement of Transient Receptor Potential Cation Channel Vanilloid 1 (TRPV1) in Myoblast Fusion. Issue 10 (8th March 2016) - Kurosaka, Mitsutoshi; Ogura, Yuji; Funabashi, Toshiya; Akema, Tatsuo
Abstract : The mechanisms that underlie the complex process of muscle regeneration after injury remain unknown. Transient receptor potential cation channel vanilloid 1 (TRPV1) is expressed in several cell types, including skeletal muscle, and is activated by high temperature and by certain molecules secreted during tissue inflammation. Severe inflammation and local temperature perturbations are induced during muscle regeneration, which suggests that TRPV1 might be activated and involved in the process. The aim of this study, was to clarify the role of TRPV1 in the myogenic potential of satellite cells responsible for muscle regeneration. We found that mRNA and protein levels of TRPV1 increased during regeneration after cardiotoxin (CTX)‐induced muscle injury in mice. Using isolated mouse satellite cells (i.e., myoblasts), we observed that activation of TRPV1 by its agonist capsaicin (CAP) augmented myogenin protein levels. Whereas CAP did not alter myoblast proliferation, it facilitated myoblast fusion (evaluated using myonucleii number per myotube and fusion index). In contrast, suppression of TRPV1 by siRNA impaired myoblast fusion. Using mice, we also demonstrated that intramuscular injection of CAP facilitated muscle repair after CTX‐induced muscle injury. Moreover, we showed that these roles of TRPV1 might be mediated by interleukin‐4 and calcium signaling during myoblast fusion. Collectively, these results suggest that TRPV1 underlies normal myogenesis through promotion of myoblast fusion. J. Cell. Physiol. 231: 2275–2285, 2016. © 2016 Wiley Periodicals, Inc.